Banks and early deposit withdrawals in a new Keynesian framework - Alexander Totzek (Kiel University, Department of Economics, 2009)
When the current financial crisis has widened to a global economic crisis an urgent call for implementing financial markets and financial institutions in business cycle models emerged. By modelling commercial banks as a third type of economic agent, we are able to implement the feature of early deposit withdrawals in a New Keynesian model and to investigate the resulting implications for the real sector. The main results are that an extended withdrawal rate leads to persistent stagflationary effects which are dampened by reducing the refinancing costs of the banking sector and by increasing the loan rate stickiness.
Keywords: E12; E44; E50; G01; 330; commercial banks; financial crises; deposit withdrawal; Bankenkrise; Einlagengeschäft; Vertrauen; Kosten; Schock; Ungleichgewichtstheorie; Cash-in-Advance-Modell; Stagflation; Theorie